The New American Catholic History - Rischin, Moses (Church history, 1972)
Even historians and historically minded Sociologists with little sense or awareness of the current Roman Catholic scene have been stirred by the precipitous flow of events of the last dozen years to ask questions about the Catholic role in American society. Virtually without warning, the history of American Catholicism has been catapulted from specialized ecclesiastical history of interest to Catholics primarily into an ecumenical history of unprecedented general interest. After hovering backstage for centuries, the Catholic presence has erupted almost simultaneously from the secular and theological wings and burst onto centerstage. A convergence of public events dramatized and personalized for world Catholicism by the papacy of John XXIII and for American Catholicism by the presidency of John F. Kennedy ironically magnified a sense of supreme Catholic crisis and confusion that in its scope and implications dwarfed earlier American Catholic crises, making them appear parochial and intramural by comparison. The elevation to the papacy of the most saintly and humble of priests and the brief presidency of the first Catholic president of the United States turned an aged pope and a young president into symbols of a new public Catholicism, cosmopolitan and courageous in its vision and democratic in its thrust. Vatican II, the ecumenical movement, the race revolution, the general revolt against authority, the new ethnic succession, explosive social and geographic mobility, and the heightened self-consciousness of newer ethnics of European origin and largely Catholic religion, combined with the instant exposure of the mass media, synchronized with an era of American world hegemony and the emergence of an American Catholicism of appropriate dimensions.